"Efectos de tres intensidades de poda en dos variedades (Nacio0nal y trinitario) de cacao (Theobroma caca L.) establecidos con tres métodos propagativos, en la finca experimental "La Represa" - Moreno Cano, Cinthia Johanna (2018)
Three intensities of pruning were evaluated in two varieties (National and Trinitarian) of cacao (Theobroma cacao L.) established with three propagative methods, in the Experimental Farm "La Represa" owned by the State Technical University of Quevedo, where a complete random design was used within a bifactorial arrangement, as the first pruning factor with three pruning intensities (without pruning, moderate pruning, drastic pruning), as the second cocoa propagation factor, with 3 repetitions and 5 experimental units of each treatment in study, with the purpose of evaluating the three pruning intensities, on the productive parameters (number of healthy ears (nms), fresh weight, total ears) Yield kg / ha-1 / year) sanitary variables (number of witch's brooms (eb) , number of diseased ears (nme), indexes of physical quality of the cocoa (seed index, number of almonds in 100 g, percentage of seed coat, length and width of the kernel) and cut test (percentage of fermentation) Within the productive parameters, the treatments that stood out were T9 (Moderate pruning, IMC-67-Injection CCN-51), indicating the highest number of healthy ears, the highest number of total ears and the best yields kg / ha-1 / year, concluding that the pruning did not affect the productive variables, the T18 (Drastic pruning, Ramilla CCN-51) obtaining the least number of diseased ears and witch brooms followed, In physical quality of the almond When analyzing the physical quality factors of the almonds the T5 (without pruning, EET-103 - Graft EET-103) I present the highest value in the highest index of seed, number of 100g of almonds and in the length and width of the almondaccording to these results, the pruning affected the physical quality of the almond. When performing the cutting test, the treatments that showed the highest percentages of T16 fermentation (drastic pruning, IMC-67 - CCN-51 graft), which concluded that the pruning did not affect the almond cutting test going above 80 % and getting to be located in the ASSPS category (Top Top Summer Selected.). Keywords: pruning, propagative methods, productive parameters